Mapping Research on Learning Models Lesson Study: A Bibliometric Study - Auliah, Army; Cahyani, Vika; Islawati; Fikroh, Retno Aliyatul; Rahmi Faradisya Ekapti, Rahmi Faradisya Ekapti; Lukmanul Hakim Samada, Lukmanul Hakim Samada; Nurul Ilmi, Nurul Ilmi (Universitas Negeri Padang, 2025)
The body of lesson study research necessitates a comprehensive mapping of its development in academia. Bibliometric analysis tracks the evolution and research patterns of the lesson study learning model over time. This study aims to investigate lesson study development through a three-stage process: data collection using Publish or Perish and Mendeley, bibliometric analysis with VOSviewer, and final interpretation and discussion. Findings indicate that Lesson Study and Lesson Study for Learning Community are central in educational literature, with high frequency and strong associations with other keywords. Publication trends from 2015 to 2025 show fluctuations, with spikes in 2020 and 2023. Early research emphasized teacher competencies, while trends integrate Problem-Based Learning, 21st-century skills, and collaborative professional learning, offering insights for education stakeholders.